Analisis Kesiapan Koperasi Santri (KOPSAN) Di Pondok Pesantren Al-Mu'awanah Menuju Sertifikasi Halal - Susi Nurul Fadillah; Yulianti Yulianti; Ateng Supriatna; Tri Cahyanto (Jurnal Akuntan Publik, 2023)
The purpose of this study is to evaluate the readiness of cooperatives at the Al-Mu'awanah Islamic Boarding School in applying for halal certification for each of their goods. The results of the knowledge of cooperative management about UUJPH are 81% in the good category, SJH knowledge is 90% in the good category, and HACCP knowledge is 85% in the good category, measuring the level of adaptation of cooperatives to halal-certified cooperatives at the Al-Mu'awannah Islamic Boarding School, with 85% in the good category and ready for halal certification. With this readiness, Al-Mu'awannah Islamic Boarding School is believed to be able to provide the best halal product services to customers and the surrounding community.